DEVELOPMENT OF WORDWALL-BASED LEARNING MEDIA TO IMPROVE SPEAKING SKILLS IN CHILDREN WITH SPEECH DELAY - Eti Gustini; Irma Yuliantina (Adisam Publisher, 2025)
This study aims to develop and validate interactive learning media based on Wordwall.net to improve the speaking skills of children with speech delay at TPA Aamillah Daycare, Bekasi. The research adopts the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) and focuses on the initial three stages: analysis, design, and development. The participants involved three experts: a media expert, an early childhood education expert, and a speech therapist, who were engaged to validate the feasibility of the developed media. Data collection was conducted using expert validation instruments, and the results were analyzed quantitatively using descriptive statistics. The findings revealed that the developed media was highly feasible for use in early childhood educational settings. The media expert rated the product at 91.07%, the early childhood education expert at 92.31%, and the speech therapist at 90.38%, all indicating a “very feasible” category. The conclusion highlights that the Wordwall.net-based learning media is effective and suitable for supporting speaking skill development in children with speech delay. This research contributes to the field by integrating technology with instructional design principles to create inclusive, engaging, and developmentally appropriate learning tools. The media has the potential to be implemented as a supplementary resource in both educational and therapeutic contexts, with future research needed to examine its effectiveness through direct application with the target children.